Efeito do dopante nas propriedades estruturais e magnéticas de nanopartículas de Ni1-xAxO (A=Fe e Cr) - Moura, Karoline Oliveira (2012)
In this work we have studied the structural and magnetic properties in Ni1-xAxO nanoparticles (x=0, 0,01, 0,05 e 0,10 e A=Fe ,Cr), with size from 5 to 38 nm, synthesized by co-precipitation method. In the first part we study the process of growth of the NiO nanoparticles in different synthesis conditions (influence of chelating agent and synthesis temperature). The magnetization and X-ray diffraction results showed a decreasing in the average particle size and size distribution with the increase of synthesis temperature. In the second part of this work was studied the influence of doping in the structural and magnetic properties. These results showed a decrease in particle size and change in particle shape with increasing of doping concentration. The hysteresis results show the appearance of exchange bias, which is reduced with the increasing of doping concentration, in which can be associated with increasing of thickness shell ferromagnetic of the particles. The Zero Field Cooling and Field Cooling (ZFC-FC) magnetization curves indicate for doped samples, a superparamagnetic behavior at high temperature and a uncommon peak at low temperature (close to 10 K) which is evidenced with increasing of the doping concentration, in contrast to pure sample. This behavior can be explained considering a high surface anisotropy due to the freezing of disordered surface spins caused by the incorporation of ions of Fe (or Cr) in the NiO matrix.